An Evaluation of Sex-Specific Pharmacokinetics and Bioavailability of Kokusaginine: An In Vitro and In Vivo Investigation - Kaiqi Shang; Chengyu Ge; Yindi Zhang; Jing Xiao; Shao Liu; Yueping Jiang (MDPI AG, 2024)
Kokusaginine is a bioactive ingredient extracted from Ruta graveolens L., which has a range of biological activities. Its pharmacokinetic (PK) properties are particularly important for clinical applications; however, they have not been fully elucidated. In addition, the effect of sex differences on drug metabolism is increasingly being recognized, but most studies have ignored this important factor. This study aims to fill this knowledge gap by taking an in-depth look at the PK properties of kokusaginine and how gender affects its metabolism and distribution in the body. It also lays the foundation for clinical drug development. In this study, a sensitive ultra-high-performance liquid chromatography (UPLC) method was developed and validated for quantifying kokusaginine in Sprague Dawley (SD) rat plasma and tissue homogenates. Metabolic stability was evaluated in vitro using gender-specific liver microsomes. Innovatively, we incorporated sex as a variable into both in vitro and in vivo PK studies in SD rats, analyzing key parameters with Phoenix 8.3.5 software. The developed UPLC method demonstrated high sensitivity and precision, essential for PK analysis. Notably, in vitro studies revealed a pronounced sex-dependent metabolic variability (p < 0.05). In vivo, gender significantly affected the Area Under the Moment Curve (AUMC)(0-∞) of the plasma PK parameter (p < 0.05) and the AUMC(0-t) of brain tissue (p < 0.0001), underscoring the necessity of sex-specific PK assessments. The calculated absolute bioavailability of 71.13 ± 12.75% confirmed the favorable oral absorption of kokusaginine. Additionally, our innovative tissue-plasma partition coefficient (Kp) analysis highlighted a rapid and uniform tissue distribution pattern. This study presents a sex-inclusive PK evaluation of kokusaginine, offering novel insights into its metabolic profile and distribution. These findings are instrumental for informing clinical medication practices, dosage optimization, and a nuanced understanding of drug efficacy and safety in a sex-specific context.